Early childhood care and education at the margins African perspectives on birth to three - Ebrahim, Hasina Banu; Okwany, Auma; Barry, Oumar (Routledge research in early childhood education, 2019)
"The importance of early care and education in the lives of very young children is gaining increasing attention around the globe and yet there is a persistent lack of diverse knowledge perspectives on this critical phase. This stems from dominant Eurocentric framings of early childhood research, and related theories. Early Childhood Care and Education at the Margins provides contextual accounts of early childhood care and education (ECCE) in Africa in order to build multiple perspectives on ECCE and to promote responsive thought and actions"...